Coded excitation for diverging wave cardiac imaging: a feasibility study. (27th January 2017) - Zhao, Feifei; Tong, Ling; He, Qiong; Luo, Jianwen
Abstract: Diverging wave (DW) based cardiac imaging has gained increasing interest in recent years given its capacity to achieve ultrahigh frame rate. However, the signal-to-noise ratio (SNR), contrast, and penetration depth of the resulting B-mode images are typically low as DWs spread energy over a large region. Coded excitation is known to be capable of increasing the SNR and penetration for ultrasound imaging. The aim of this study was therefore to test the feasibility of applying coded excitation in DW imaging to improve the corresponding SNR, contrast and penetration depth. To this end, two types of codes, i.e. a linear frequency modulated chirp code and a set of complementary Golay codes were tested in three different DW imaging schemes, i.e. 1 angle DW transmit without compounding, 3 and 5 angles DW transmits with coherent compounding. The performances (SNR, contrast ratio (CR), contrast-to-noise ratio (CNR), and penetration) of different imaging schemes were investigated by means of simulations and in vitro experiments. As for benchmark, corresponding DW imaging schemes with regular pulsed excitation as well as the conventional focused imaging scheme were also included. The results showed that the SNR was improved by about 10 dB using coded excitation while the penetration depth was increased by 2.5 cm and 1.8 cm using chirp code and Golay codes, respectively. The CNR and CR gains varied with the depth for different DW schemes using coded excitations. Specifically, for non-compounded DW imaging schemes, the gain in the CR was about 5 dB and 3 dB while the gain in the CNR was about 4.5 dB and 3.5 dB at larger depths using chirp code and Golay codes, respectively. For compounded imaging schemes, using coded excitation, the gain in the penetration and contrast were relatively smaller compared to non-compounded ones. Overall, these findings indicated the feasibility of coded excitation in improving the image quality of DW imaging. Preliminary in vivo cardiac images of a healthy volunteer were presented finally, and higher SNR and deeper penetration depth can be achieved by coded schemes.